The Role Of Sharia Pawnshops In The Increasing MSME Capital And Community Income (Study of The Takengon Branch Service Unit, Central Aceh) - Murni, Seri; Wahyusari, Ika (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2024)
The development of Micro, Small and Medium Enterprises or MSMEs is growing rapidly in Indonesia, including in Takengon. This also makes business actors need capital, one of which is through a pawn system. Because Aceh has made all financial institutions sharia legal, the focus role in this case is Sharia Pawnshops. This research uses a descriptive qualitative method which refers to the product marketing strategy at Sharia Pawnshops which has succeeded in increasing customer interest through socialization, promotions and advertising. This product is an Ar-Rahn product. With the continuity of all this, this also influences the increase in community income.